Acidovorax citrulli Type III Effector AopP Suppresses Plant Immunity by Targeting the Watermelon Transcription Factor WRKY6 - Zhang, Xiaoxiao; Yang, Yuwen; Zhao, Mei; Yang, Linlin; Jiang, Jie; Walcott, Ron; Yang, Shanshan; Zhao, Tingchang (Frontiers in Plant Science, 2020)
Acidovorax citrulli (Ac) is the causal agent of bacterial fruit blotch (BFB), and BFB poses a threat to global watermelon production. Despite its economic importance, the molecular mechanisms underlying Ac pathogenicity and virulence are not well understood, particularly with regard to its type III secreted effectors. We identify a new effector, AopP, in Ac and confirm its secretion and translocation. AopP suppresses reactive oxygen species burst and salicylic acid (SA) content and significantly contributes to virulence. Interestingly, AopP interacts with a watermelon transcription factor, ClWRKY6, in vivo and in vitro. ClWRKY6 shows typical nuclear localization, and AopP and ClWRKY6 co-localize in the nucleus. Ac infection, SA, and the pathogen-associated molecular pattern flg22Ac promote ClWRKY6 production, suggesting that ClWRKY6 is involved in plant immunity and SA signaling. Furthermore, ClWRKY6 positively regulates PTI and SA production when expressed in Nicotiana benthamiana. Importantly, AopP reduces ClWRKY6 mRNA and ClWRKY6 protein levels, suggesting that AopP suppresses plant immunity by targeting ClWRKY6. In summary, we identify a novel effector associated with the virulence mechanism of Ac, which interacts with the transcription factor of the natural host, watermelon. The findings of this study provide insights into the mechanisms of watermelon immune responses and may facilitate molecular breeding for bacterial fruit blotch resistance.